Robotic knitcrete: computational design and fabrication of a pedestrian bridge using robotic shotcrete on a 3D-Knitted formwork - Rennen, Philipp; Gantner, Stefan; Dielemans, Gido; Bleker, Lazlo; Christidi, Nikoletta; Dörrie, Robin; Hojjat, Majid; Mai, Inka; Mawas, Karam; Lowke, Dirk; D’Acunto, Pierluigi; Dörfler, Kathrin; et al. (Frontiers in Built Environment, 2023)
The research project presented here aims to develop a design-informed manufacturing process for complex concrete shell structures in additive manufacturing and thus overcome limitations of traditional construction methods such as formwork- and labor intensity. To achieve this, an effort was made to merge the two technologies of CNC knitted stay-in-place formwork, known as KnitCrete, and robotically applied shotcrete, known as Shotcrete 3D Printing (SC3DP), and thereby reduce their respective limitations. The proposed workflow unites both digital fabrication methods into a seamless process that additionally integrates computational form finding, robotically applied fiber reinforcement, CNC post processing and geometric quality verification to ensure precision and efficiency. As part of a cross-university, research-based teaching format, this concept was implemented in the construction of a full-scale pedestrian bridge, which served as a demonstrator to evaluate the capabilities and limitations of the process. While overcoming some challenges during the process, the successful prove of concept shows a significant leap in digital fabrication of complex concrete geometry, reducing reliance on labor-intensive methods. The results shown in this paper make this fabrication approach a promising starting point for further developments in additive manufacturing in the construction sector.